PEMBUATAN APOTEK HIDUP, PUPUK ORGANIK CAIR, DAN PESTISIDA NABATI DALAM RANGKA UPAYA MEMENUHI TANAMAN OBAT KELUARGA DAN PERKEBUNAN BERKELANJUATAN DI DESA BUNTU BAYU KEC. HATONDUHAN - Saroha Manurung; Alfinda Julianto; Akbar Dwi Purnama; Anri Arjuna Simbolon; Dea Rizky Agustina A; Umar Bakri Hasibuan; Veny Wina Lestari H (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This community service initiative aimed to enhance the self-sufficiency of Buntu Bayu Village by establishing home pharmacies, producing liquid organic fertilizer (POC), and creating botanical pesticides. Participatory training and hands-on practices were employed, utilizing local resources such as medicinal plants, organic waste, and natural ingredients for pesticides. The results demonstrated increased community awareness in utilizing home gardens for medicinal plants, reduced reliance on chemical fertilizers through POC, and the effectiveness of botanical pesticides in pest control. The program not only supported family health and sustainable agriculture but also created economic opportunities based on local wisdom.